Pengaruh Kepemimpinan Manajer Public Relations terhadap Kualitas Manajemen Public Relations dan Korelasinya dengan Efektivitas Sistem Komunikasi Perusahaan - Yulianita, Neni (Mediator, 2002)
The focus of this research was to study the personal skills and leadership functions of the public relations manager which is assumed will bear its influence on the quality of public relations management in order to enhance the effectiveness of the communication system of his organization. The approach used in this research was systems approach in the social-science context which is interlaced with interdicipliner approach from the psychology, communication, sociology,and management perspective. As for the method used was ""the Explanatory Survey Method"".  The research object was conducted in 19 BUMN in DKI Jakarta and West Java. Tocollect the data, the researcher used questionnaires, in depth interview, observation, and library study. The questionnaires were distributed to 85 respondents among Public Relations Officers (PRO) and 96 respondents among corporate managers. To fullflll the research data, the researcher took in depth interview to 19 public relations manager from selected BUMN. The conclusion from the result of hypothesis using Path AnalySis-Statistical Test and ProductMoment Correlation Coefficient r ofident that either the main hypothesis or subhypotheses proposed were accepted. The leadership (Viewed from the aspect of personal skills and leadership function) of Public Relations Manager among BUMN significantly influenced the quality of Public Relations Management and the quality of PR Manajement had significantly correlation with the effectiveness of a corporate communication system.